Cellular - Papadaki, M. (IEEE Engineering in medicine and biology magazine)
This work presents the challenges and directions in biomaterials research. Biomaterials have been playing an important role in the treatment of disease and the improvement of healthcare. Metals were used in dentistry while synthetic polymers have been used for vascular grafts; polymethylmethacrylate and stainless steel have been used in total hip replacements. Controlled drug delivery systems largely involve biomedical polymers and are used by tens of million of people annually. Furthermore, in tissue engineering, by combining polymers with mammalian cells, it is now possible to engineer skin for patients who have burns or skin ulcers. Until recently, biomaterials were adopted from other areas of science and technology with little design for biomedical use, which did not help to completely resolve issues in biocompatibility, mechanical properties, degradation, etc. Modern biomaterial science is laying the foundation for a fundamental design by taking into consideration cell-matrix interactions, cellular signaling processes, and developmental biology. Concepts that are shaping future directions are biomaterials for specific biomedical applications made from naturally occurring or man-made building blocks or novel applications for biomaterials, such as diagnostics and array technologies.